(untitled) (Archive of Conferences, 2020)
socio-political changes on a global, regional, local scale, affecting the change of values, way of thinking, beliefs of people, and, at the same time, strengthening the indicators of political reflection of events, phenomena, processes, etc., actualize the problem of political consciousness and behavior